Reforma al art. 663, numeral 3 del código orgánico integral penal, referente a la conciliación en los delitos contra la propiedad - Reyes Sarango, Jorge Luis (2017)
The present research work whose theme is "REFORM TO ART 663, NUMERAL 3 OF THE ORGANIC CRIMINAL INTEGRAL CODE, CONCILIATION IN THE CRIMES AGAINST PROPERTY", it is considered necessary the reform to this legal body, taking into consideration that at no Existing legislation violates the right to legitimate defense of persons taking into account that it is feasible and very important that there is conciliation in crimes against property if the parties will agree. The fact of living in a social conglomerate; And to be subject to preset norms that are constantly transgressed by the human being, has affected the typification of negative behaviors, which the Integral Criminal Organic Code has collected them, as regards the alternative means that in this case is the Conciliation, We must express the agility and timely speed with which conflicts are resolved. Since always there were mechanisms of solution without regard to the economic amount of the infraction, since what was fundamental was the spirit of solving the problem, however; Nowadays the legislator establishes a limitation to be able to make use of the conciliation, being a social problem that affects the society. In the Ecuadorian Penal Regime different mechanisms and procedures have been envisaged for the solution of conflicts. Thus, in the Code of Criminal Integral, the typification of some alternative means, and conciliation has been classified as one of the best options, because As a third party is involved, the decision is exclusively those involved in the conflict. The present thesis of Legal Investigation is structured as follows: In the first place a Conceptual Framework, which includes concepts and definitions of Sanctions, Penalties, Crimes and thus defining the experts so as to know their functions; A Doctrinal Framework, which covers the doctrines of the writers and scholars about how experts influence the evidence in a process, then addresses a Legal Framework, which includes the analysis of the Constitution of the Republic of Ecuador, the Treaties and International Conventions, the Organic Integrated Criminal Code, the Organic Code of Judicial Function and then we have a Comparative Legislation, since it served to me to make an analysis of the labor issue of other countries and to extract the most positive thing. Secondly the research work comprises a field study in which surveys and interviews are developed to those who know the law in which they help me to determine or contrast the objectives and hypotheses raised. In the third place after the analysis of the field research, the conclusions and recommendations were made and finally a legal proposal necessary to solve the problem